Microsporogenesis and anther development in Bromeliaceae - Sajo, M. G.; Furness, C. A.; Prychid, C. J.; Rudall, P. J. (Taylor & Francis As, 2005)
Bromeliaceae possess several features of pollen and anther wall development that are plesiomorphic for Poales, consistent with their putatively basal or near-basal placement in this order. For example, successive microsporogenesis and the monocotyledonous type of anther wall formation are both plesiomorphic features that occur commonly in other Poales, with a few notable exceptions, notably the simultaneous type of microsporogenesis in Rapateaceae. The intermediate type of tapetum development in Bromeliaceae was probably derived secondarily from a secretory type, which occurs in most other Poales except Typhaceae.